Cloning of cDNA-gene of Arabidopsis thaliana ribosomal protein S6, its expression in Escherichia coli and purification of AtRPS6B1 recombinant protein - Nadirova, L.T.; Beisenov, D.K.; Stanbekova , G.E.; Zhigailov , A.V.; Ryabova , L.A.; Iskakov , B.K. (Eurasian Journal of Applied Biotechnology, 2024)
Ribosomal protein S6 is a component of the 40S small ribosomal subunit and plays an important role in protein biosynthesis. Its main function is related to the regulation of mechanisms that control cell growth and division. The RPS6 can be phosphorylated on defined serine and threonine residues by kinases such as S6K1 and S6K2, which in turn are activated by signaling pathways associated with the activation of the mTORC1 molecular complex. The phosphorylation process of protein RPS6 plays a key role in the regulation of cell growth and protein synthesis. Activated RPS6 protein influences translation initiation, which means start the process of protein synthesis on the ribosome. Thus, RPS6 is associated with the regulation of cell size and their ability to divide. In addition, the RPS6 protein can be associated with other proteins and participate in various molecular interactions, which may vary depending on the context of cellular activity. In this study, cloning and site-directed cDNA mutagenesis of the second isoform of the AtRPS6 protein (AtRPS6B) was performed. Further, the obtained phosphomimetic and nonphosphorylated forms of this protein were expressed in E.coli ArcticExpress (DE3) cells, the proteins were purified by metal chelate chromatography (IMAC) and the presence and purity of the obtained proteins was confirmed by immunoblotting